Evidence for an inhibitory-control theory of the reasoning brain - Houdé, Olivier; Borst, Grégoire (Frontiers in Human Neuroscience, 2015)
In this article, we first describe our general inhibitory-control theory and, then, we describe how we have tested its specific hypotheses on reasoning with brain imaging techniques in adults and children. The innovative part of this perspective lies in its attempt to come up with a brain-based synthesis of Jean Piaget’s theory on logical algorithms and Daniel Kahneman’s theory on intuitive heuristics.